Functional and radiological outcome of surgical treatment of distal tibial fracture by minimally invasive percutaneous plate osteosynthesis technique - H.P., Shobha; S., Karthik; Dhanda, Akshay; K., Lingaraju; Kumar, Giridhar (International Journal of Research in Orthopaedics, 2020)
Background: Minimally invasive percutaneous plate osteosynthesis (MIPPO) is an established technique for fixation of fractures of the distal third tibia. Aim of our study was to manage extraarticular fractures of the distal third tibia by the minimally invasive plate osteosynthesis technique and follow them prospectively. Clinical and radiological outcomes were studied and clinical indications & efficacy of the procedure reviewed. Methods: From June 2018 to June 2019,25 patients of closed distal tibial fractures were operated by MIPPO technique with a distal tibial anatomical locking plate having 4.5 out of 5 proximal and 3.5 out of 4 distal screw holes. The follow up duration was for 1 year. Results: The mean fracture healing time was 17 weeks (range 16 to 32 weeks) and average The American orthopedic foot and ankle score was 88.2 out of a total possible 100 points. At last follow up, superficial infection occurred in 3 patients, deep infection in 1 patient, ankle stiffness in 1 patient, limb length discrepancy <1 cm in 1 patient and malunion in 2 patients. Conclusions: MIPPO technique provides good bone healing and decreases incidence of non-union and need for bone grafting. This technique should be used in distal tibia fractures where locked nailing cannot be done like fractures with small distal metaphyseal fragments, vertical splits, markedly comminute fractures.